Strategies for Supporting Healthcare Workers’ Resilience and Mental Health During A Pandemic: A Scoping Review - Eka Oktavianto; I Made Moh. Yanuar Saifudin; Gani Apriningtyas Budiyati (Jurnal Keperawatan Indonesia, 2023)
As a group, health workers are at risk of experiencing stress and mental health problems at work, which may negatively affect their resilience. This study assessed the effectiveness of mental health support strategies for health workers during the COVID-19 pandemic. This scoping review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines in searching through three journal databases, such as: EBSCO, Scopus, and PubMed. The quality of the studies was assessed with the Crowe Critical Appraisal Tool, and the results of the review emerged from a process of synthesis that identified common themes. The search yielded five main articles. The results of the synthesis process inspired several recommended strategies to support the resilience and mental health of health workers during a pandemic, including personal management, psychoeducational, and counselling approaches. It is important to work in partnership with stakeholders and across sectors to derive the maximum benefit from these interventions. Abstrak Strategi untuk Mendukung Resiliensi dan Kesehatan Mental Tenaga Kesehatan saat Pandemi: Scoping Review. Tenaga kesehatan adalah kelompok dengan risiko mengalami masalah kesehatan mental, seperti stress, di tempat kerja yang dapat berdampak negatif pada ketahanan/resiliensi. Tinjauan literatur ini bertujuan untuk menilai efektifitas strategi pendukung kesehatan mental tenaga kesehatan selama pandemi COVID-19. Scoping review dilakukan dengan menggunakan PRISMA guidelines dalam melakukan pencarian pada tiga database jurnal, yaitu EBSCO, Scopus dan PubMed. Kualitas studi dinilai dengan Crowe Critical Appraisal Tool. Hasil ulasan diformulasikan melalui proses narasi berulang dari hasil sintesis untuk mengidentifikasi tema umum. Pencarian pada tiga database menghasilkan lima artikel utama. Melalui proses sintesis, didapatkan beberapa strategi yang diketahui efektif dalam meningkatkan kesehatan mental tenaga kesehatan. Strategi yang dimaksud dapat berupa manajemen pribadi, kegiatan konseling bersama ahli, dan pelatihan/pendidikan terkait manajemen stres. dukungan stakeholder dan lintas sektor menjadi hal yang penting untuk memaksimalkan manfaat intervensi. Kata Kunci: tenaga kesehatan, kesehatan mental, pandemi, resiliensi